Negotiable instruments : laws and application for business students - Soriano, Fidelito R. (Recto, Manila : Conanan Educational Supply, 2011)
The first edition of Negotiable Instruments (Law and Application) has been written primarily for the use of business students, particularly those preparing for the CPA Licensure Examination. The book discusses the legal principles using the "section-explanation-example approach" illustrating the points involved with practical and case-based examples. Each provision is explained not in isolation, but in correlation with other legal principles, thereby enabling the student to better understand the law since he gets to see it in a broader perspective.
Introduction -- Negotiable Instruments in General -- Form and Interpretation -- Consideration -- Negotiation -- Rights of Holder -- Liabilities of Parties -- Presentment for Payment -- Notice of Dishonor -- Discharge of Negotiable Instruments -- Bills of Exchange -- Form and Interpretation --Acceptance -- Presentment for Acceptance -- Protest -- Acceptance for Honor 2--Payment for Honor -- Bills in Set -- Promissory Notes and Checks -- General Provisions -- Diagnostic Exercises -- Answer to Diagnostic Exercises --
Keywords: NEGIOTIABLE INSTRUMENTS -- PHILIPPINES